Teachers role in creating siblings social behavior in age differented groups following example of Lodz’s University Preschool - Kowalczyk, Anna; Sosnowska, Joanna (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
The preschool age is the time when a child is preparing to go to school. It is a transition period when he or she gets to know the life outside of a family house, but it not yet fully independent. A preschool is an institution where children spend the most of their time, which is why that place is so significant in the process of children’s socialization. Peer relationships comprise a source of the unique experiences for children who feel more responsible for cooperation with each other than with adults. The institutions which function on the basis of innovative ideas of upbringing, for example Montessori preschools, provide education for groups of children at relatively varied age, that is for 3-, 4-, 5- and 6-year olds. In such a group, which creates more natural and favourable conditions for development, children provide one another a range of emotional, social and intellectual experiences. In this article, there have been included the outcomes of the research on the way of siblings’ functioning in the preschool age-varied groups.